PENGARUH SOSIALISASI PAJAK, PENGETAHUAN PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PELAKU E-COMMERCE (Studi Kasus Pada Pengusaha Online Shopping di Kota Malang) - Sania Septianingrum (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine whether tax socialization, tax knowledge, and taxpayer awareness have an effect on taxpayer compliance with e-commerce actors. Sources of data in this study using primary data with data collection through online questionnaires. Sampling was based on the purposive sampling method, namely e-commerce actors or online shopping entrepreneurs in the city of Malang in the fashion sector who are willing to be respondents and have been operating for at least 1 year. The number of questionnaires that were processed were 40 respondents. The data analysis methods used are: descriptive dtatistics, data quality test, classical assumption test, multiple linear regression analysis, hypothesis testing and processed using SPSS version 23. The results of this study indicate that tax socialization, tax knowledge, and taxpayer awareness have a significant effect. Simultaneous compliance with taxpayers of e-commerce actors. Tax socialization and tax knowledge have a positive and significant effect on e-commerce taxpayer compliance, while taxpayer awareness has no effect on e-commerce taxpayer compliance.Keywords: tax socialization, tax knowledge, taxpayer awareness, taxpayer compliance, e-commerce actors.